2011
DOI: 10.1161/circulationaha.111.027813
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adipose Tissue Oxygen Tension in Obese Compared With Lean Men Is Accompanied by Insulin Resistance, Impaired Adipose Tissue Capillarization, and Inflammation

Abstract: Background-Adipose tissue (AT) dysfunction in obesity contributes to chronic, low-grade inflammation that predisposes to type 2 diabetes mellitus and cardiovascular disease. Recent in vitro studies suggest that AT hypoxia may induce inflammation. We hypothesized that adipose tissue blood flow (ATBF) regulates AT oxygen partial pressure (AT PO 2 ), thereby affecting AT inflammation and insulin sensitivity. Methods and Results-We developed an optochemical measurement system for continuous monitoring of AT PO 2 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
275
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(298 citation statements)
references
References 49 publications
17
275
5
1
Order By: Relevance
“…Furthermore, it has been reported that this tissue is under chronic hypoxic conditions during the development of obesity [22,48], although a situation of decreased adipose tissue oxygen tension in obese compared to lean men may not always occur [18], which would be explained by a lower adipose tissue oxygen consumption. This hypoxic state is linked to an increase in pro-inflammatory cytokine release in adipocytes, while anti-inflammatory adipokines such as adiponectin are often decreased [60].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that this tissue is under chronic hypoxic conditions during the development of obesity [22,48], although a situation of decreased adipose tissue oxygen tension in obese compared to lean men may not always occur [18], which would be explained by a lower adipose tissue oxygen consumption. This hypoxic state is linked to an increase in pro-inflammatory cytokine release in adipocytes, while anti-inflammatory adipokines such as adiponectin are often decreased [60].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence for reduced oxygen tension in adipose tissue of obese humans (Pasarica et al, 2009), although a recent report has challenged this view (Goossens et al, 2011). Hypoxia leads to important functional changes in adipocyte metabolism, including an increase in glucose utilisation Yin et al, 2009) and lactate production (Pérez de Heredia et al, 2010), indicative of enhanced glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility is supported by the finding that adipocytes can secrete numerous potent pro-angiogenic factors, some in response to hypoxia (11), and that VEGF-A expression can mitigate the development of metabolic dysfunction in response to a high fat diet (HFD) 2 (12,13). However, recent studies suggest that hypoxia of adipose tissue may not reach levels sufficient to elicit a pro-angiogenic response (14) and that expression of HIF-1␣ in adipocytes results in fibrosis rather than angiogenesis (15).…”
mentioning
confidence: 99%